The role of wood decay fungi in the carbon and nitrogen dynamics of the forest floor - Watkinson, S; Bebber, D; Darrah, P; Fricker, M; Tlalka, M; Boddy, L (Cambridge University Press, 2006)
Introduction The mycelium of woodland fungi can act both as a reservoir and as a distribution system for nutrients, owing to its physiological and developmental adaptations to life at the interface between organic and mineral soil horizons. The mobility of accumulated nitrogen and phosphorus within the mycelial networks of cord-forming wood decay fungi and ectomycorrhiza enables fungi to play key roles as wood decomposers and root symbionts. The dynamics of nitrogen movement have been less investigated than phosphorus owing to lack of a suitable tracer. We have developed a new technique for tracing nitrogen translocation in real time, using 14C as a marker for nitrogen by incorporating it into a nondecomposed amino acid that tracks the mycelial free amino acid pool. Its movement can be imaged by counting photon emissions from a scintillant screen in contact with the mycelial system. This method allows real-time imaging at high temporal and spatial resolution, for periods of weeks and areas up to 1m2, in microcosms that mimic the mineral/organic soil interface of the forest floor. The results reveal a hitherto unsuspected dynamism and responsiveness in amino acid flows through mycelial networks of cord-forming, wood-decomposing basidiomycetes. We interpret these in the light of current understanding of the pivotal role of fungi in boreal and temperate forest floor nutrient cycling, and attempt to formulate key questions to investigate the effects of mycelial nitrogen translocation on forest floor decomposition and nitrogen absorption.